EPC/TURNKEY CONTRACT, LUMPSUM FIXED PRICE SUBJECT TO ADJUSTMENTS - Hardjomuljadi, Sarwono (Konstruksia, 2015)
The most important thing before starting the construction project is deciding the type of contract will be used for the projectâs implementation. In order to get the proper decision, the understanding on various conditions of contracts are required. In Indonesia there are many project using the so called âmodifiedâ FIDIC Conditions of Contract for EPC/Turnkey Project, but with the incorrect understanding on the reasons of using EPC/Turnkey Contract, so instead of solving the problem it may caused bigger problems in practice, many problems raised during the execution due to such incorrect understanding of the spirit of EPC/Turnkey Contract. Most of Employers, in this case the government institution or state owned enterprises in Indonesia, choose the EPC/Turnkey Contract with minimum understanding of the essence of the EPC/Turnkey Contract. Their reasons of choosing the EPC/Turnkey Contract was the âtied scheduleâ and the âhigher certainty of costâ. FIDIC EPC/Turnkey Contract based on the discussion in this paper, instead of fit the Employerâs need only, the EPC/Turnkey Contract still give chance to the contractor to submit their claim (Clause 20) and even the price is fixed, payment could be made once the claim is accepted (Sub-Clause 17.4) means that additional to the contract price can be done. One of the important noteworthy thing is that if there is additional cost it should be âadded to the contract priceâ, while in the conventional contract it should be âincluded in the contract priceâ, so the final price will be the same (Sub-Clause 14.1).Â Keyword: EPC/Turnkey Contract, tied schedule, higher certainty of cost, added, included.